# Prove that cot4x (sin5x + sin3x) = cot x (sin5x – sin3x)

To prove cot4x (sin5x + sin3x) = cot x (sin5x – sin3x)

LHS = cot 4x (sin 5x + sin 3x)

We know,

LHS = cot 4x × 2 sin 4x × cos x

LHS = 2 cos 4x cos x

RHS = cot x (sin 5x – sin 3x)

We know,

RHS = cot x × 2 cos 4x × sin x

RHS = 2 cos 4x cos x

LHS = RHS

Hence, proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Trigonometric Functions - 0568 mins
Trigonometric Functions - 0152 mins
Graphs of trigonometric ratios | Trigonometric Identities39 mins
Trigo ratios for compound angles48 mins
Quiz on Graph of Trigonometric Ratios40 mins
Conditional Identities31 mins
Transformation formula in compound angles | Interactive Quiz37 mins
Trigonometry ratios of allied angles | Interactive Quiz38 mins
Trigonometric Functions - 0658 mins
Trigonometric Series45 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

If A + B + C = π, prove that

RS Aggarwal - Mathematics

If A + B + C = π, prove that

RS Aggarwal - Mathematics